Cognitive and Emotional Determinants of Sustainable Engagement with Digital Clothing - Xujie Zhu; Sook Jin Kim (Environment and Social Psychology, 2025)
Fast fashion, textile waste, and overproduction create serious sustainability issues for the fashion industry. Digital clothing, also known as virtual fashion, incorporates augmented reality, social media, and the metaverse. This form of virtual fashion has the potential to reduce the harmful impact on the environment caused by fast fashion. This research involves a systematic literature review with thematic analysis (based on the model suggested by Braun and Clarke) to explore the cognitive and emotional variables involved in digital clothing sustainability. The study focuses on 28 peer-reviewed articles published between 2014 and 2025, focusing on digital clothing. The key cognitive determinants are perceived usefulness, digital literacy, and sustainability awareness that constitute the rational basis of adoption decisions. Emotional determinants, including expression of identity, hedonic joy, and social belonging, were necessary to long-term engagement. Several barriers exist, including the intangible nature of digital garments and doubts over their authenticity and sustainability. Results indicate that there is a need for an approach that combines both emotional and rational factors of customer motivation. This helps to understand how consumers make decisions and stay engaged over time with digital clothing. Consequently, the digital clothing businesses need to deliver a trustworthy, engaging, customized, and sustainable way to attract customers. At the same time, educating customers on digital literacy is essential in the long term. Moreover, policymakers should develop inclusive policies that ensure sustainability and digital equity in the digital fashion industry. Collectively, the measures can help form a supportive environment for sustainable and digital engagement in the fashion industry.